If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16h + (-14h) + (-3h) = 9 Combine like terms: 16h + (-14h) = 2h 2h + (-3h) = 9 Combine like terms: 2h + (-3h) = -1h -1h = 9 Solving -1h = 9 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '-1'. h = -9 Simplifying h = -9
| 3x^2(6x)= | | 18v-15v-v-v=19 | | 10w-5w=20 | | 20b-14b=18 | | 2m+7m=9 | | 9x+n=x^2 | | 4(k+4)=20 | | -22+3x-(-2)=-2x | | 3(j-5)+1=10 | | 2/s=1 | | 2(d-13)-11=1 | | 2n^2=-n+3 | | j-2/2=2 | | 15/x=.55 | | 4/d=2 | | 7+9g=25 | | -42=q/6-47 | | c(c-7)=0 | | 13=g/3-(-11) | | 0=25-10x^2 | | -3+(-n)=-7 | | x^2-4x+9=2 | | 3x^2+40x-2000=0 | | 2=4+(-2p) | | 13-2b=1 | | 1200=18(5t-1.5) | | 8=2-(-2t) | | 15ab+[(6ab-c)+(4ab+c)]= | | 8=2-(-2) | | M=-1/2;(-3,0) | | M÷-1/2;(-3,0) | | 6=3r-(-3) |